A Study on Quality of Work Life and Employee Motivational Strategies - Shankar, J.Vignesh, (International Journal of Scientific Research and Management (IJSRM), 2014)
The main purpose of this paper is to investigate and determine the quality of work life and motivation ofemployees and their effects on organizational operations in Export Industries. To reach the quality of worklife mostly depends upon making regular attempts from an organization, which provides their employeeswith more opportunities so that they can be more effective in their organization. Quality in an organization isdefined as an advantage, as a value, as determination of conformity and as meeting customer’s expectations.Good quality of work life is necessary for an organization to attract and to retain skilled and talentedemployees. Employees are the most important assets of any organizations and its success or failure dependson their qualifications and performance. In order to survive in the competitive market because ofLiberalization, Privatization and Globalization and to minimize the attrition rate of employees the quality ofwork life initiatives are very important. Motivated employees and Satisfied customers are the backbone ofany successful organizations. This paper focuses and analyzes the literature findings which involve qualityof work life and predictors of employee motivational strategies.